The impact of kangaroo Mother care on the Newborn Health Outcome of A preterm Infant at Al-Zahraa Teaching Hospital in Al-Najaf AL-Ashraf City 2024 - Worood Noaman Hadi; Ali Abdul Ridha Abutiheen; Alaa Jumaah Manji Nasrawi (مجلة الكوفة الطبية, 2025)
Background Preterm neonates are the most critical cause of death in infants, Kangaroo Mother Care is an important early distinctive care with the least expensive piece of equipment to permit the health and well-being of infants born, by holding neonates on the mother's naked chest with skin-skin contact and exclusive breastfeeding involved with early home discharge. WHO recommended KMC for all neonates, especially preterm. Methods: A prospective cohort, observational design study of preterm infants, the study included a sample of 100 neonates (50 of them subjected to kangaroo groups, the remaining 50 were control group) delivered in AL-Zahraa teaching hospital with birth weight of less than 2000gm and gestational age of 28–35 weeks of both group, Consecutive sample was used to collect the data, all mothers of preterm babies were involved and interviewed with a predesigned questionnaire to take information about her and the neonates, after discharge home each preterm neonates were followed-up for six months age, comparison have been occurred between preterm admitted to kangaroo mother care unit and preterm neonates who didn’t admit. Result: KMC infants as opposed to control group demonstrated Weight gain by (90%) RR 1.55(95%CI 1.2-1.99). and (90%) length increment RR 2.50(95%CI 1.7-3.5), (100%) exclusively breast fed, infant's developmental activities revealed (100%) RR 2.77(95%CI 1.9-4.0), the mean duration of hospital admission of Kangaroo group was (7.47±1.05) while, the case group (11.28±5.05), a P-value  of all these follow up variations are statistically significant (<0.001). Conclusion: Results yield that KMC is one of the essential, inexpensive methods; it has the potential effects that significantly improve the newborns' physiological outcomes, increase neonatal survival, improve maternal-infant attachment, and encourage early hospital discharge.